(2‐Aminopyrimidine‐κN1)aqua(pyridine‐2, 6‐dicarboxylato‐κ3O2, N, O6)copper(II): X‐ray and DFT calculated structure. Issue 5 (14th April 2015) - Yousefi, Zakieh; Eshtiagh‐Hosseini, Hossein; Salimi, Alireza; Soleimannejad, Janet
<x xml:space="preserve">Abstract</x> In the title compound, [Cu(C7H3N2O4)(C4H5N2)(H2O)], (I), pyridine‐2, 6‐dicarboxylate (pydc2−), 2‐aminopyrimidine and aqua ligands coordinate the CuII centre through two N atoms, two carboxylate O atoms and one water O atom, respectively, to give a nominally distorted square‐pyramidal coordination geometry, a common arrangement for copper complexes containing the pydc2− ligand. Because of the presence of Cu...Xbridged contacts (X = N or O) between adjacent molecules in the crystal structures of (I) and three analogous previously reported compounds, and the corresponding uncertainty about the effective coordination number of the CuII centre, density functional theory (DFT) calculations were used to elucidate the degree of covalency in these contacts. The calculated Wiberg and Mayer bond‐order indices reveal that the Cu...O contact can be considered as a coordination bond, whereas the amine group forming a Cu...N contact is not an effective participant in the coordination environment.